Study of gamma radiation shielding on tellurite glass containing TiO2 and Al2O3 nanoparticles - Floressy Juhim; Fuei Pien Chee; Asmahani Awang; Pak Yan Moh; Khairul Anuar Mohd Salleh; Sofian Ibrahim; Jedol Dayou; Amani Alalawi; M.S. Al-Buriahi (Elsevier, 2023)
Radiation shielding incorporates material between the radioactive source and environment to decrease exposure to hazardous radiation. It remains to be seen whether the addition of nanoparticles effectively increases the protection of tellurite glass system from further degradation under irradiation conditions. This study revealed the gamma radiation effects on tellurite glass. The tellurite glass samples were irradiated with 50 kGy and 100 kGy gamma ray, and subsequently analysed using X-ray diffractometer (XRD), atomic force microscopy (AFM), and ultraviolet–visible spectroscopy (UV–Vis). Gamma radiation increased the creation of non-bridging oxygen (NBO) and caused colour change on TZNETi and TZNETiAl glasses. Consequently, the addition of aluminium oxides (Al2O3) was found to lower the density of glass systems. The glass samples surface roughness increased, while the optical transmission spectra decreased after 50 kGy of gamma ray irradiation. Nevertheless, the glass system maintained its transparency even after irradiation. The mass attenuation coefficient (MAC) values represented the shielding effectiveness demonstrated by the investigated glass with the addition of Al2O3. The physical, structural, optical, and radiation shielding properties showed that 69.1TeO2–20ZnO–9Na2O–1Er2O3–0.3TiO2–0.6Al2O3 (TZNETiAl) sample exhibited strong shielding properties amongst the fabricated tellurite samples.